2006
DOI: 10.4081/hi.2006.94
|View full text |Cite
|
Sign up to set email alerts
|

AngioJet thrombectomy for the treatment of coronary artery aneurysm after failed thrombolysis in acute myocardial infarction

Abstract: Acute myocardial infarction (AMI) is caused by thrombus formation over a disrupted plaque occluding an epicardial coronary artery. Mechanical thrombectomy is effective in removing thrombus burden from native vessels and saphenous vein grafts. Here we report a case of an aneurysmatic dilatation of an infarct-related artery (IRA) referred to our Institute for rescue PCI, after failed fibrinolysis, successfully treated with only rheolytic thrombectomy (AngioJet, Possis Medical, Minneapolis, Minnesota, USA) withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Owing to the high burden of related thrombosis, thrombus aspiration is often performed as additional therapy. 11 Our patient had a large thrombus in the dilated right coronary artery, and thrombus aspiration was incomplete. Therefore, we performed intracoronary thrombolysis, and right coronary artery blood flow reached thrombus in myocardial infarction (TIMI) level 3, with only a small amount of the thrombus remaining.…”
Section: Discussionmentioning
confidence: 73%
“…Owing to the high burden of related thrombosis, thrombus aspiration is often performed as additional therapy. 11 Our patient had a large thrombus in the dilated right coronary artery, and thrombus aspiration was incomplete. Therefore, we performed intracoronary thrombolysis, and right coronary artery blood flow reached thrombus in myocardial infarction (TIMI) level 3, with only a small amount of the thrombus remaining.…”
Section: Discussionmentioning
confidence: 73%
“…To avoid this phenomenon in the presence of a high-burden thrombus during ACS, some case reports described more specific approaches. Giombolini et al [21] reported the usefulness of the rheolytic thrombectomy system AngioJet to remove soft material immediately before PCI or stenting permitting identification of lesion specifics and more sitespecific treatment of the underlying culprit lesion, particularly in patients with total occlusion. A few case reports described the use of an aspiration catheter.…”
Section: Discussionmentioning
confidence: 99%
“…Rheolytic thrombectomy techniques, specifically the AngioJet percutaneous mechanical thrombectomy system, initially create a fluid suction by introducing high-pressure saline and pro-thrombotic medication through catheter openings around the target, which produces a subsequent inwards flow, aspirating the resultant debris as the devices move proximally in the clot [8]. The thrombus is subsequently fragmented by jets as it enters the catheter, which introduces thrombolytics [9][10][11]. The AngioJet thrombectomy portfolio is used across the spectrum of embolic and thrombotic events, being implemented in large arteries and targeting coronary occlusions, with respective systems designed for each use case that has a different working length [12].…”
Section: Introductionmentioning
confidence: 99%